1995
DOI: 10.1161/01.cir.92.9.174
|View full text |Cite
|
Sign up to set email alerts
|

Target Heart Failure Populations for Newer Therapies

Abstract: Ambulatory populations with high predicted event rates can be identified at initial evaluation, when hemodynamic criteria may be less useful than ventricular dimension, serum sodium, and ability to exercise. The use of outcome data from previous eras may lead to overestimation of benefits from newer therapies and underestimation of the sample size required in a prospective trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
3

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(16 citation statements)
references
References 20 publications
0
13
0
3
Order By: Relevance
“…20 However, others have suggested that prognosis bears little relationship to more direct measures of cardiac performance. 16,19,24 We thus suspect that over a long-term follow-up, those with a low initial aerobic power progress more quickly to the point where pump function becomes inadequate. Another possibility is that an individual's peak V O 2 influences the proportion of aerobic power used during heavy activities and thus the vulnerability to catecholamine-induced arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…20 However, others have suggested that prognosis bears little relationship to more direct measures of cardiac performance. 16,19,24 We thus suspect that over a long-term follow-up, those with a low initial aerobic power progress more quickly to the point where pump function becomes inadequate. Another possibility is that an individual's peak V O 2 influences the proportion of aerobic power used during heavy activities and thus the vulnerability to catecholamine-induced arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…1 Several new biomarkers have emerged as strong predictors of risk among patients presenting with cardiovascular disease, including CHF. Among them, cardiac troponin I (cTnI) and T, 2 B-type natriuretic peptide (BNP), 3 N-terminal pro-B-type natriuretic peptide (NT-proBNP) 4 and high-sensitivity C-reactive protein (hsCRP) 5,6 are easy to measure and such measurement is now routinely available to clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…Esses valores contrastam positivamente com publicações recentes sobre pacientes avaliados para tratamento cirúrgico da insuficiência cardíaca, que mostram uma probabilidade de sobrevida ao redor de 50% em dois anos, para pacientes que estavam inicialmente em classe funcional III ou IV (30) .…”
Section: Fatores Relacionados Ao Prognósticounclassified
“…Esse fato aponta para a limitação da indicação da ventriculectomia parcial apenas para pacientes que tenham um comprometimento menos severo da função ventricular esquerda. No entanto, esses pacientes têm apresentado, atualmente, uma evolução satisfatória com a otimização da terapêutica medicamentosa (30) , ficando a indicação de procedimentos cirúrgicos paliativos restrita apenas àqueles que evoluem com piora progressiva de sua qualidade de vida ou da tolerância ao exercício. A influência da condição clínica pré-operatória dos pacientes sobre os resultados imediatos da ventriculectomia parcial já havia sido sugerida por BESTETTI et al (3) e por McCARTHY et al (12) , sendo também observada por KAWAGUSHI et al (9) em dados obtidos em 172 pacientes de um registro multicêntrico internacional.…”
Section: Fatores Relacionados Ao Prognósticounclassified